Differences in the effects of age on the development of entheseal changes among historical Japanese populations. Issue 2 (26th September 2015) - Yonemoto, Shiori
ABSTRACT: Objective: This study aims to determine the impacts of both age and physical activity on entheseal changes at sites of muscle and ligament attachment, and proposes that the influence of age on entheseal changes may depend on specific social systems. Methods: Entheseal markers of 193 individuals excavated from archaeological sites in Japan were examined, and archaeological evidence from those sites was used to determine the subsistence activities that those individuals engaged in. Fifteenth‐century samples were either fishermen or Agehamashiki salt manufacturers, while samples from between the late 17 th century and the 19 th century were peasants, townspeople, or samurai . Nineteen entheses were examined using the scoring method of Hawkey and Merbs (1995) to clarify the degree to which age influenced entheseal severity of a given sample as well as the differences in the degree to which age influenced entheseal changes among samples. Results: Results indicated that age influenced entheseal changes; however, the degree to which age influenced entheseal development was dependent on the characteristic physical activities associated with an individual's class and occupation. Furthermore, in certain groups, aging did not significantly impact entheseal changes. Discussion: The degree to which age influenced entheseal changes was dependent on characteristic physical activities associated with an individual's class and occupation. This indicated that physical activities and lifestyle, along with age, were major factors that contributed to entheseal changes. Based on these results, it was concluded that entheseal changes could serve as a useful tool in the reconstruction of physical activities of past populations. Am J Phys Anthropol 159:267–283, 2016. © 2015 Wiley Periodicals, Inc.